Librarian on the roof! : a true story - King, M. G. (Miriam Grace), 1968-; Gilpin, Stephen (Chicago : Albert Whitman, 2010)
RoseAleta Laurell, the new library at the Dr. Eugene Clark Library in Lockhart, Texas, the oldest library in the state, decides to raise money to make a special place for children by spending a week on the roof of the building.
2.9
K-3
Keywords: Dr. Eugene Clark Library -- Juvenile literature; Public libraries -- Texas -- Lockhart -- History -- 20th century -- Juvenile literature; Laurell, RoseAleta -- Juvenile literature; Dr. Eugene Clark Library; Public libraries -- History; Laurell, RoseAleta; Dr. Eugene Clark Library; Public libraries -- Lockhart (Tex.) -- History; Laurell, RoseAleta; Picture books for children